The Roman bridge between Dolni Vadin (Bulgaria) and Grojdibodu (Romania) - Bondoc, Dorel (Archaeopress Roman archaeology, 2018)
This volume contains all the available data on the Roman bridge over the Danube which connected Dolni Vadin (Bulgaria) and Grojdibodu (Romania) that the author was able to access given the fact that there have been no archaeological excavations at the feet of the bridge.